Rethinking Socialism and Fascism in post-Yugoslav cinemas - Borjan, Etami (2012)
Although the war was the dominant topic in the film production of the post-Socialist period, a small number of the so called “revisionist” movies were produced. Originally works, mostly docu-dramas, mocumentaries and feature films, offer examples of different approach to the official historical “truths” related to Socialism and fascism. Two outspoken critics of the Serbian nationalist regime ; Želimir Žilnik (Tito drugi put medu Srbima, Tito among the Serbs for the Second Time, 1994) and Goran Marković (Tito i ja, Tito and I, 1992), and the famous Croatian blockbuster maker Vinko Brešan (Maršal, Marshall Tito, 1999), questioned the role of Tito and the ways in which his image was perceived after the Yugoslavia’s breakup. All films are intentionally provocative and sarcastic in their aim to demonstrate the ambiguity of the Yugoslav history as a politically conditioned social and ideological construct.